Relational Aggression and Depressive Symptoms: The Mediating Role of Social Exclusion Perception - Ben Amor, Leila; Maisarah, Syarifah (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to examine the mediating role of social exclusion perception in the relationship between relational aggression and depressive symptoms among Malaysian adolescents. Methods and Materials: A descriptive correlational design was employed with a sample of 383 secondary school students in Malaysia, selected based on Krejcie and Morgan’s sample size determination table. Data were collected using standardized self-report instruments measuring relational aggression, social exclusion perception, and depressive symptoms. Descriptive statistics and Pearson correlation analyses were performed using SPSS-27. Structural Equation Modeling (SEM) was conducted using AMOS-21 to assess the hypothesized mediation model and evaluate model fit through indices such as CFI, TLI, RMSEA, and χ²/df. Findings: Results indicated that relational aggression was significantly and positively correlated with both social exclusion perception (r = .49, p < .001) and depressive symptoms (r = .42, p < .001), while social exclusion perception was also strongly correlated with depressive symptoms (r = .55, p < .001). SEM analysis demonstrated an acceptable model fit (χ²/df = 2.34, CFI = 0.96, RMSEA = 0.058), supporting the proposed mediational model. Path analysis revealed that relational aggression had a significant direct effect on depressive symptoms (β = 0.26, p < .001), as well as an indirect effect through social exclusion perception (β = 0.27, p < .001), with a total effect of β = 0.53. These results support the role of perceived social exclusion as a partial mediator in the association between relational aggression and depressive symptomatology. Conclusion: The findings underscore the importance of perceived social exclusion as a psychological mechanism linking relational aggression to depressive symptoms in adolescents. Addressing exclusion experiences in peer interactions may be critical in designing effective interventions to reduce depression and promote emotional well-being among youth.